First Total Synthesis of a Cytotoxic Derivative of the Natural Product Aaptamine - Puvvala, Srinu; Jadhav, Vinod D.; Narkhede, Umesh C.; Anji Karun, M. V. V. S. R. N.; Venkata Ramana Reddy, Ch. (Synthesis, 2017)
A synthetic sequence to the benzonaphthyridinone framework is described. The key step is a one-pot, base-catalyzed vicarious nucleophilic substitution followed by ring closure. Additionally, the synthesis represents the application of a vicarious nucleophilic substitution in the total synthesis of a cytotoxic aaptamine derivative.
Keywords: total synthesis; heterocycles; vicarious aromatic substitution; cyclization; alkylation